Botulinum toxin type A and gabapentin attenuate postoperative pain and NK1 receptor internalization in rats. (June 2018) - Li, Xueyang; Guo, Ruijuan; Sun, Yuqing; Li, Huili; Ma, Danxu; Zhang, Chen; Guan, Yun; Li, Junfa; Wang, Yun
Abstract: Treatment of postoperative pain remains a challenge in clinic. Botulinum toxin type A (BoNT/A) and gabapentin regulate the release of neurotransmitters from primary afferent neurons, but their effects of on postoperative pain are not clear. In the current study, using pain behavioral tests, Western blot analysis, and immunocytochemistry, we examined whether BoNT/A, alone or in combination with intrathecal gabapentin, inhibited pain hypersensitivity and attenuated the increase in neurokinin 1 (NK1) receptor internalization in dorsal horn neurons after plantar incision. Our data showed that pretreatment of rats with an intraplantar (2 U) 24 h before plantar incision or intrathecal (0.5 U) injection of BoNT/A 48 h before plantar incision induced a prolonged (3–5 days) decrease in pain scores and mechanical hypersensitivity, as compared to those observed with saline pretreatment. Both intraplantar and intrathecal BoNT/A pretreatment reduced synaptosomal-associated protein 25 levels in the ipsilateral lumbar dorsal root ganglia and spinal cord dorsal horn, and attenuated the increase in NK1 receptor internalization in dorsal horn neurons. Intrathecal administration of a sub-effective dose of gabapentin (50 μg) with BoNT/A (0.5 U) induced greater inhibition of pain hypersensitivity and NK1 receptor internalization than BoNT/A alone. These findings suggest that pretreatment with BoNT/A, alone or in combination with intrathecal gabapentin, may present a promising multimodal analgesia regimen for postoperative pain treatment. Highlights: Intraplantar or intrathecal BoNT/A induced a persistent pain relief after incision. Intraplantar or intrathecal BoNT/A inhibited the incision-induced substance P release from primary afferent terminals. Intrathecal gabapentin and BoNT/A in combination more effectively reduced substance P release from primary afferent terminals. Intrathecal gabapentin and BoNT/A in combination provided more pain relief in incisional rats.